The effect of morphometry, viscosity and liquefaction on frozen sperm quality of Ghezel ram - parisa shafaati (Islamic Azad University, Tabriz Branch, 2021)
The ability of sperm to move and reach the oocyte for fertilization and fertility depends on different factors such as morphometry, liquefaction and semen viscosity. The present study was performed to evaluate the effect of morphometry, viscosity and liquefaction of semen on Ghezel ram frozen sperm quality. Semen was collected once a week for 3 weeks from 5 Ghezel rams. Initial assessments included total and progressive motility, viability, abnormal sperm percentage, concentration, viscosity, morphometry, and liquefaction. Samples with a concentration of 2.5 billion sperm and a progressive motility of over 70% were used for dilution. After dilution, straws (0.25 ml) were filled and after cooling and reaching the temperature of 5°C in the refrigerator, were placed 4-5 cm above liquid nitrogen for 8-10 min and then, ultimately were immersed in liquid nitrogen. The traits of motility and sperm health were assessed on days 0, 20, 40 and 60 of cryopreservation. The results showed that motility traits and viability were significantly reduced over time of cryopreservation (p<0.05). Furthermore, the results of this study showed a negative and significant correlation between drop length and plasma membrane health (p<0.05). Also, it was shown that there was a positive and significant correlation between semen string length and total motility (p<0.01). There was a significant negative correlation between liquefaction and total motility, progressive motility, viability and acrosome integrity (p<0.01). There was a significant negative correlation between tail length and total sperm length with plasma membrane health (p<0.01). The findings of the present study indicated that the shorter the liquefaction time, sperm tail length and total length of sperm, the qualitative traits of sperm will be better preserved in the freezing process.